Analisis Performa Jaringan Sensor Nirkabel Berdasarkan Penentuan Lokasi Node Yang Telah Diimplementasikan Dengan Algoritma Genetika - Irma Asri Kartika Sandy; Mochammad Hannats Hanafi Ichsan; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The critical success factor of communication in a wireless sensor network is the connectivity of the sensor nodes in the network. Connectivity of the sensor nodes depends on the position of the sensor nodes, so in the design of wireless sensor network need to pay attention to the laying of sensor nodes in order to improve the performance of sensor networks. Genetic Algorithm is a method that has a bending property that can be used to determine the position of the node. There are studies using genetic algorithms to determine the best position that has not been implemented. Therefore, the implementation and analysis on the performance of wireless sensor networks that laying the node has been implemented with genetic algorithm. Analysis is done by analyzing the value of quality of service (delay, jitter, throughput) from communication between nodes to user's computer, and by analyzing test result from 5 channel flame sensor coverage area. And to make the previous system become dynamic, the feature is added. The result of the analysis shows the value of quality of service delay of 7.66 s. The value of jitter is 1.01 and the value of throughput is 77.01. Analysis of the 5 channel flame sensor test results is the sensor can cover with a distance of more than 100 cm with medium or large fire volume. Test results from the system to be more dynamic has a 100% success, that is by adding features of the radius input section of the sensor and the room width according to user needs.